Charles Correa: Architect in India - Khan, Hasan-uddin (2008)
Hasan-Uddin Khan's book is more than a mere showcase of buildings; it's a deep dive into the ideas that shaped Charles Correa's career. The book emphasizes Correa's philosophy of "open-to-sky space," which was a direct response to India's climate and cultural traditions. He masterfully blended modernist principles with local sensibilities, using elements like courtyards, verandas, and natural ventilation to create spaces that were both functionally modern and culturally rooted.
Part of the "Architects in the Third World" series. Includes essays by Sherban Cantacuzino and Charles Correa.
Keywords: Architecture -- India -- History -- 20th century; Correa, Charles, 1930-2015 -- Criticism and interpretation; Modern architecture -- India; Urban planning